1 - La dépendance en héritage au Burkina Faso: L'économie avant la révolution - Kamadini OUALI, (Africa Development, 1986)
In this paper, the author looks into the problem of the depen dency of Burkina Faso economy before the popular and democm tic revolution of August 4, 1983 started. In the first part, he makes a survey of the recent developments in the economic theories of dependency and development. In the subsequent parts, he discusses the issues of transfer of human capital as well as structural constraints concerning direct investments, monetary flows, export structures and the capacity for technology innovation. He concludes his study with some recommendations for the pros pects of the implementation of a strategy for independen